The Role of IT (Information Technology) Audit in Digital Transformation: Opportunities and Challenges - Mirwali Azizi; Hakimi, Musawer; Frishta Amiri; Amir Kror Shahidzay (Open Access Indonesia Journal of Social Sciences, 2024)
The study explores into the ramifications of digital transformation on IT audit practices, scrutinizing both the opportunities and challenges faced by organizations globally. Its objective is to bolster the efficacy of IT audit by identifying pivotal insights and furnishing recommendations for adaptation. By thoroughly examining existing literature and synthesizing key findings, the study endeavors to shed light on how organizations can harness IT audit to optimize the advantages of digital transformation while mitigating associated risks. Conducting an exhaustive literature review, the research probes the impact of digital transformation on IT audit, drawing from esteemed sources to dissect the evolving role, avenues for improvement, and obstacles encountered. The results underscore the imperative of recalibrating IT audit practices to effectively contend with burgeoning technological demands. The literature illuminates a significant metamorphosis in IT audit prompted by the adoption of digital technologies. While prospects include advancements in data analytics, automation, and strategic advisory roles, challenges loom large in the form of cybersecurity risks and resource constraints. Ultimately, the study underscores the exigency for IT audit to adapt to technological advancements while navigating intricate challenges to sustain its effectiveness. In conclusion, digital transformation necessitates a proactive reorientation of IT audit practices to confront emerging risks head-on. Leveraging data analytics and strategic roles bolsters effectiveness, yet addressing cybersecurity and resource constraints mandates proactive measures and strategic investments. Organizations can optimize the value of digital transformation by fortifying IT audit through proactive initiatives and nurturing talent development.